Characterization of high temperature solar thermal system using non-imaging focusing heliostat - Loh, Ying Zhe (2021)
The spinning-elevation method first suggested by Ries and Zaibel and in 2001, Chen et al. proposed a non-imaging focusing heliostat (NFIH) implementing the spinningelevation method which capable of actively correcting the astigmatic aberration that exists in the traditional heliostat system. Since then, Chen et al. and Chong have collectively derived and developed the sun-tracking formula for the NIFH. In the thesis, formulas derived will be utilized to the simulation for the NIFH. The optimal simulated result within the shortest period are investigated and the factors that affect the efficiency of the NIFH such as circumsolar ratio ( CSR) and slope error (SE) were studied and results show that with increased of CSR and SE, the spillage loss increases, heliostat efficiency dropped and causing a deviation to the flux distribution profile of the NIFH.